Minimum wage and tax evasion: Theory and evidence - Mirco Tonin (Institute for the Study of Labor (IZA), 2011)
This paper examines the interaction between minimum wage legislation and tax evasion by employed labor. I develop a model in which firms and workers may agree to report less than the true amount of earnings to the fiscal authorities. I show that introducing a minimum wage creates a spike in the distribution of declared earnings and induces higher compliance by some agents, thus reducing their disposable income. The comparison of food consumption and of the consumption-income gap before and after the massive minimum wage hike that took place in Hungary in 2001 reveals that households who appeared to benefit from the hike actually experienced a drop compared to similar but unaffected households, thus supporting the prediction of the theory.
urn:nbn:de:101:1-201104283153
Keywords: J38; H24; H26; H32; 330; minimum wage; tax evasion; spike; Hungary; Mindestlohn; Steuervermeidung; Schattenwirtschaft; Lohndifferenzierung; Ungarn